Cloud management and monitoring - a systematic mapping study - Isaac Odun-Ayo; Toro-Abasi Williams; Jamaiah Yahaya (Institute of Advanced Engineering and Science, 2021)
A key component of ensuring that services are available on the cloud at the right time in the right manner is adequate cloud management. This makes it possible to provide services that meets user demands. The purpose of this research is to carry out a systematic study of management and monitoring on the cloud. Three facets were applied in conducting the categorization. These are the contribution, research, and topic facets. The purpose was to determine the level of work so far carried out in the field of cloud management. This enabled the creation of a pictorial representation of the research coverage. The result of the study showed that there are no opinion research on cloud management. Generally, articles on experience research, philosophical research and metric are the lowest at 6.62%, 4.41% and 1.90% respectively, while articles on models, solution research and evaluation research are the highest with 52.38%, 46.32% and 31.62% respectively. The outcome of this study will stimulate further research in the area cloud management and systematic studies.